Artificial intelligence and extended reality in luxury fashion retail: Analysis and reflection - Loureiro, S. M. C. (Augmented reality and artificial intelligence: The fusion of advanced technologies, 2023)
Retailing service is facing a rapid evolution through the incorporation of Extended Reality (XR) technologies and Artificial Intelligence (AI) algorithms. Within this umbrella, one can consider all real-and-virtual combined environments and interactions generated by computer, including Augmented Reality (AR), Mixed Reality (MR) and Virtual Reality (VR). This chapter brings together research on the experience of luxury fashion consumer retail and AI and XR technologies to identify critical gaps and open avenues for future research. It aims to analyse the incorporation and the potential evolution of AI and XR technologies in luxury fashion retail. The chapter presents the main theoretical concepts and the luxury fashion consumption cycle and offers a discuss about the human and non-human rights, privacy, and ethics at three levels: mega, micro, and nano. Also, the chapter contributes with a discussion about the rights, privacy and ethics involving humans, hybrid humans, and non-humans.